Using a developmental perspective to examine the moderating effects of marriage on heavy episodic drinking in a young adult sample enriched for risk. (August 2021) - Cho, Seung Bin; Smith, Rebecca L.; Bucholz, Kathleen; Chan, Grace; Edenberg, Howard J.; Hesselbrock, Victor; Kramer, John; McCutcheon, Vivia V.; Nurnberger, John; Schuckit, Marc; Zang, Yong; Dick, Danielle M.; et al.
Abstract: Many studies demonstrate that marriage protects against risky alcohol use and moderates genetic influences on alcohol outcomes; however, previous work has not considered these effects from a developmental perspective or in high-risk individuals. These represent important gaps, as it cannot be assumed that marriage has uniform effects across development or in high-risk samples. We took a longitudinal developmental approach to examine whether marital status was associated with heavy episodic drinking (HED), and whether marital status moderated polygenic influences on HED. Our sample included 937 individuals (53.25% female) from the Collaborative Study on the Genetics of Alcoholism who reported their HED and marital status biennially between the ages of 21 and 25. Polygenic risk scores (PRS) were derived from a genome-wide association study of alcohol consumption. Marital status was not associated with HED; however, we observed pathogenic gene-by-environment effects that changed across young adulthood. Among those who married young (age 21), individuals with higher PRS reported more HED; however, these effects decayed over time. The same pattern was found in supplementary analyses using parental history of alcohol use disorder as the index of genetic liability. Our findings indicate that early marriage may exacerbate risk for those with higher polygenic load.